Search for blocks/addresses/...
Proofgold Address
address
PURznaAAQp4Y7VWtq1o8tgV4t8GySAbj2eU
total
0
mg
-
conjpub
-
current assets
ffbf3..
/
acdf0..
bday:
35045
doc published by
PrNpY..
Param
real
real
:
ι
Param
setexp
setexp
:
ι
→
ι
→
ι
Param
SNoS_
SNoS_
:
ι
→
ι
Param
omega
omega
:
ι
Param
SNoLt
SNoLt
:
ι
→
ι
→
ο
Param
ap
ap
:
ι
→
ι
→
ι
Param
add_SNo
add_SNo
:
ι
→
ι
→
ι
Param
eps_
eps_
:
ι
→
ι
Param
minus_SNo
minus_SNo
:
ι
→
ι
Param
SNo
SNo
:
ι
→
ο
Param
abs_SNo
abs_SNo
:
ι
→
ι
Known
real_add_SNo
real_add_SNo
:
∀ x0 .
x0
∈
real
⟶
∀ x1 .
x1
∈
real
⟶
add_SNo
x0
x1
∈
real
Theorem
34bd0..
Conj_real_add_SNo__44__7
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
x2
∈
setexp
(
SNoS_
omega
)
omega
⟶
x3
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
x4
∈
setexp
(
SNoS_
omega
)
omega
⟶
x5
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Param
ordsucc
ordsucc
:
ι
→
ι
Theorem
c4ebc..
Conj_real_add_SNo__43__10
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
x2
∈
setexp
(
SNoS_
omega
)
omega
⟶
x3
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
x5
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
59aa9..
Conj_real_add_SNo__40__19
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
x3
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
x5
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
bce5d..
Conj_real_add_SNo__41__9
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
x3
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
x5
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
d6042..
Conj_real_add_SNo__40__2
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
x5
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
786e0..
Conj_real_add_SNo__37__9
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
x5
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x3
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x3
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x5
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
5c476..
Conj_real_add_SNo__36__12
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x3
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x3
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x5
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
ec53b..
Conj_real_add_SNo__36__15
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x3
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x3
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x5
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Param
SNoLev
SNoLev
:
ι
→
ι
Param
setprod
setprod
:
ι
→
ι
→
ι
Param
SNoL
SNoL
:
ι
→
ι
Param
SNoR
SNoR
:
ι
→
ι
Param
SNoCut
SNoCut
:
ι
→
ι
→
ι
Param
binunion
binunion
:
ι
→
ι
→
ι
Theorem
7cb2e..
Conj_mul_SNo_eq__25__3
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
SNo
x0
⟶
SNo
x1
⟶
(
∀ x4 .
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x5 .
SNo
x5
⟶
x2
x4
x5
=
x3
x4
x5
)
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
⟶
SNoCut
(
binunion
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
)
(
binunion
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
)
=
SNoCut
(
binunion
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
)
(
binunion
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
)
(proof)
Theorem
7e49d..
Conj_mul_SNo_eq__25__0
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
SNo
x1
⟶
(
∀ x4 .
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x5 .
SNo
x5
⟶
x2
x4
x5
=
x3
x4
x5
)
⟶
(
∀ x4 .
x4
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x4
=
x3
x0
x4
)
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
⟶
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
=
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
⟶
SNoCut
(
binunion
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
)
(
binunion
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
{
add_SNo
(
x2
(
ap
x5
0
)
x1
)
(
add_SNo
(
x2
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x2
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
)
=
SNoCut
(
binunion
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoL
x1
)
}
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoR
x1
)
}
)
(
binunion
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoL
x0
)
(
SNoR
x1
)
}
{
add_SNo
(
x3
(
ap
x5
0
)
x1
)
(
add_SNo
(
x3
x0
(
ap
x5
1
)
)
(
minus_SNo
(
x3
(
ap
x5
0
)
(
ap
x5
1
)
)
)
)
|x5 ∈
setprod
(
SNoR
x0
)
(
SNoL
x1
)
}
)
(proof)
Param
Sep
Sep
:
ι
→
(
ι
→
ο
) →
ι
Definition
Subq
Subq
:=
λ x0 x1 .
∀ x2 .
x2
∈
x0
⟶
x2
∈
x1
Definition
and
and
:=
λ x0 x1 : ο .
∀ x2 : ο .
(
x0
⟶
x1
⟶
x2
)
⟶
x2
Known
andI
andI
:
∀ x0 x1 : ο .
x0
⟶
x1
⟶
and
x0
x1
Known
set_ext
set_ext
:
∀ x0 x1 .
x0
⊆
x1
⟶
x1
⊆
x0
⟶
x0
=
x1
Theorem
98ac0..
Conj_KnasterTarski_set__3__0
:
∀ x0 .
∀ x1 :
ι → ι
.
{x2 ∈
x0
|
∀ x3 .
x3
∈
prim4
x0
⟶
x1
x3
⊆
x3
⟶
x2
∈
x3
}
∈
prim4
x0
⟶
x1
{x2 ∈
x0
|
∀ x3 .
x3
∈
prim4
x0
⟶
x1
x3
⊆
x3
⟶
x2
∈
x3
}
∈
prim4
x0
⟶
(
∀ x2 .
x2
∈
prim4
x0
⟶
x1
x2
⊆
x2
⟶
{x3 ∈
x0
|
∀ x4 .
x4
∈
prim4
x0
⟶
x1
x4
⊆
x4
⟶
x3
∈
x4
}
⊆
x2
)
⟶
x1
{x2 ∈
x0
|
∀ x3 .
x3
∈
prim4
x0
⟶
x1
x3
⊆
x3
⟶
x2
∈
x3
}
⊆
{x2 ∈
x0
|
∀ x3 .
x3
∈
prim4
x0
⟶
x1
x3
⊆
x3
⟶
x2
∈
x3
}
⟶
x1
(
x1
{x2 ∈
x0
|
∀ x3 .
x3
∈
prim4
x0
⟶
x1
x3
⊆
x3
⟶
x2
∈
x3
}
)
⊆
x1
{x2 ∈
x0
|
∀ x3 .
x3
∈
prim4
x0
⟶
x1
x3
⊆
x3
⟶
x2
∈
x3
}
⟶
∀ x2 : ο .
(
∀ x3 .
and
(
x3
∈
prim4
x0
)
(
x1
x3
=
x3
)
⟶
x2
)
⟶
x2
(proof)
Definition
False
False
:=
∀ x0 : ο .
x0
Definition
not
not
:=
λ x0 : ο .
x0
⟶
False
Known
ordsuccI1
ordsuccI1
:
∀ x0 .
x0
⊆
ordsucc
x0
Theorem
24d2c..
Conj_PigeonHole_nat__1__0
:
∀ x0 .
∀ x1 :
ι → ι
.
∀ x2 x3 x4 .
x3
∈
ordsucc
(
ordsucc
x0
)
⟶
ordsucc
x4
∈
ordsucc
(
ordsucc
x0
)
⟶
not
(
x2
⊆
x3
)
⟶
x2
⊆
x4
⟶
x1
x3
=
x1
(
ordsucc
x4
)
⟶
x3
=
ordsucc
x4
⟶
∀ x5 : ο .
x5
(proof)
Param
If_i
If_i
:
ο
→
ι
→
ι
→
ι
Definition
or
or
:=
λ x0 x1 : ο .
∀ x2 : ο .
(
x0
⟶
x2
)
⟶
(
x1
⟶
x2
)
⟶
x2
Known
xm
xm
:
∀ x0 : ο .
or
x0
(
not
x0
)
Known
If_i_1
If_i_1
:
∀ x0 : ο .
∀ x1 x2 .
x0
⟶
If_i
x0
x1
x2
=
x1
Known
ordsuccE
ordsuccE
:
∀ x0 x1 .
x1
∈
ordsucc
x0
⟶
or
(
x1
∈
x0
)
(
x1
=
x0
)
Known
If_i_0
If_i_0
:
∀ x0 : ο .
∀ x1 x2 .
not
x0
⟶
If_i
x0
x1
x2
=
x2
Known
FalseE
FalseE
:
False
⟶
∀ x0 : ο .
x0
Definition
nIn
nIn
:=
λ x0 x1 .
not
(
x0
∈
x1
)
Known
In_irref
In_irref
:
∀ x0 .
nIn
x0
x0
Theorem
814b8..
Conj_PigeonHole_nat_bij__2__2
:
∀ x0 .
∀ x1 :
ι → ι
.
∀ x2 x3 x4 .
(
∀ x5 .
x5
∈
x0
⟶
∀ x6 .
x6
∈
x0
⟶
x1
x5
=
x1
x6
⟶
x5
=
x6
)
⟶
not
(
∀ x5 : ο .
(
∀ x6 .
and
(
x6
∈
x0
)
(
x1
x6
=
x2
)
⟶
x5
)
⟶
x5
)
⟶
x4
∈
ordsucc
x0
⟶
(
(
x3
=
x0
⟶
∀ x5 : ο .
x5
)
⟶
x3
∈
x0
)
⟶
If_i
(
x3
=
x0
)
x2
(
x1
x3
)
=
If_i
(
x4
=
x0
)
x2
(
x1
x4
)
⟶
x3
=
x4
(proof)
Definition
TransSet
TransSet
:=
λ x0 .
∀ x1 .
x1
∈
x0
⟶
x1
⊆
x0
Definition
ordinal
ordinal
:=
λ x0 .
and
(
TransSet
x0
)
(
∀ x1 .
x1
∈
x0
⟶
TransSet
x1
)
Param
PNo_strict_imv
PNo_strict_imv
:
(
ι
→
(
ι
→
ο
) →
ο
) →
(
ι
→
(
ι
→
ο
) →
ο
) →
ι
→
(
ι
→
ο
) →
ο
Param
PNo_strict_lowerbd
PNo_strict_lowerbd
:
(
ι
→
(
ι
→
ο
) →
ο
) →
ι
→
(
ι
→
ο
) →
ο
Param
PNo_strict_upperbd
PNo_strict_upperbd
:
(
ι
→
(
ι
→
ο
) →
ο
) →
ι
→
(
ι
→
ο
) →
ο
Param
iff
iff
:
ο
→
ο
→
ο
Known
ordinal_Hered
ordinal_Hered
:
∀ x0 .
ordinal
x0
⟶
∀ x1 .
x1
∈
x0
⟶
ordinal
x1
Theorem
d71fb..
Conj_PNo_strict_imv_pred_eq__6__3
:
∀ x0 x1 :
ι →
(
ι → ο
)
→ ο
.
∀ x2 .
∀ x3 x4 :
ι → ο
.
ordinal
x2
⟶
TransSet
x2
⟶
(
∀ x5 .
x5
∈
x2
⟶
∀ x6 :
ι → ο
.
not
(
PNo_strict_imv
x0
x1
x5
x6
)
)
⟶
PNo_strict_lowerbd
x1
x2
x3
⟶
PNo_strict_upperbd
x0
x2
x4
⟶
PNo_strict_lowerbd
x1
x2
x4
⟶
(
∀ x5 .
ordinal
x5
⟶
x5
∈
x2
⟶
iff
(
x3
x5
)
(
x4
x5
)
)
⟶
∀ x5 .
x5
∈
x2
⟶
iff
(
x3
x5
)
(
x4
x5
)
(proof)
Param
PNo_bd
PNo_bd
:
(
ι
→
(
ι
→
ο
) →
ο
) →
(
ι
→
(
ι
→
ο
) →
ο
) →
ι
Theorem
33d61..
Conj_PNo_bd_In__1__3
:
∀ x0 x1 :
ι →
(
ι → ο
)
→ ο
.
∀ x2 x3 .
∀ x4 :
ι → ο
.
(
∀ x5 .
x5
∈
PNo_bd
x0
x1
⟶
∀ x6 :
ι → ο
.
not
(
PNo_strict_imv
x0
x1
x5
x6
)
)
⟶
x3
∈
ordsucc
x2
⟶
PNo_strict_imv
x0
x1
x3
x4
⟶
not
(
x3
∈
PNo_bd
x0
x1
)
(proof)
Known
and3I
and3I
:
∀ x0 x1 x2 : ο .
x0
⟶
x1
⟶
x2
⟶
and
(
and
x0
x1
)
x2
Theorem
79465..
Conj_SNo_etaE__5__1
:
∀ x0 x1 x2 .
SNoLt
x0
x1
⟶
SNo
x1
⟶
SNoLev
x1
=
x2
⟶
SNoLev
x1
∈
SNoLev
x0
⟶
and
(
and
(
SNo
x1
)
(
SNoLev
x1
∈
SNoLev
x0
)
)
(
SNoLt
x0
x1
)
(proof)
Param
SNo_rec_i
SNo_rec_i
:
(
ι
→
(
ι
→
ι
) →
ι
) →
ι
→
ι
Param
SNo_
SNo_
:
ι
→
ι
→
ο
Known
SNoS_I
SNoS_I
:
∀ x0 .
ordinal
x0
⟶
∀ x1 x2 .
x2
∈
x0
⟶
SNo_
x2
x1
⟶
x1
∈
SNoS_
x0
Known
ordsuccI2
ordsuccI2
:
∀ x0 .
x0
∈
ordsucc
x0
Known
SNoLev_
SNoLev_
:
∀ x0 .
SNo
x0
⟶
SNo_
(
SNoLev
x0
)
x0
Known
ordinal_ordsucc
ordinal_ordsucc
:
∀ x0 .
ordinal
x0
⟶
ordinal
(
ordsucc
x0
)
Known
SNoLev_ordinal
SNoLev_ordinal
:
∀ x0 .
SNo
x0
⟶
ordinal
(
SNoLev
x0
)
Theorem
85918..
Conj_SNo_rec2_eq__1__1
:
∀ x0 :
ι →
ι →
(
ι →
ι → ι
)
→ ι
.
∀ x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 .
(
∀ x5 .
SNo
x5
⟶
∀ x6 .
SNo
x6
⟶
∀ x7 x8 :
ι →
ι → ι
.
(
∀ x9 .
x9
∈
SNoS_
(
SNoLev
x5
)
⟶
∀ x10 .
SNo
x10
⟶
x7
x9
x10
=
x8
x9
x10
)
⟶
(
∀ x9 .
x9
∈
SNoS_
(
SNoLev
x6
)
⟶
x7
x5
x9
=
x8
x5
x9
)
⟶
x0
x5
x6
x7
=
x0
x5
x6
x8
)
⟶
(
∀ x5 .
x5
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x5
=
x3
x5
)
⟶
SNo
x4
⟶
(
∀ x5 .
ordinal
x5
⟶
∀ x6 .
x6
∈
SNoS_
x5
⟶
SNo_rec_i
(
λ x8 .
λ x9 :
ι → ι
.
x0
x1
x8
(
λ x10 x11 .
If_i
(
x10
=
x1
)
(
x9
x11
)
(
x2
x10
x11
)
)
)
x6
=
SNo_rec_i
(
λ x8 .
λ x9 :
ι → ι
.
x0
x1
x8
(
λ x10 x11 .
If_i
(
x10
=
x1
)
(
x9
x11
)
(
x3
x10
x11
)
)
)
x6
)
⟶
SNo_rec_i
(
λ x6 .
λ x7 :
ι → ι
.
x0
x1
x6
(
λ x8 x9 .
If_i
(
x8
=
x1
)
(
x7
x9
)
(
x2
x8
x9
)
)
)
x4
=
SNo_rec_i
(
λ x6 .
λ x7 :
ι → ι
.
x0
x1
x6
(
λ x8 x9 .
If_i
(
x8
=
x1
)
(
x7
x9
)
(
x3
x8
x9
)
)
)
x4
(proof)
Param
SNoCutP
SNoCutP
:
ι
→
ι
→
ο
Theorem
e0a4a..
Conj_minus_SNo_prop1__2__2
:
∀ x0 x1 .
SNo
x0
⟶
(
∀ x2 .
x2
∈
SNoS_
(
SNoLev
x0
)
⟶
and
(
and
(
and
(
SNo
(
minus_SNo
x2
)
)
(
∀ x3 .
x3
∈
SNoL
x2
⟶
SNoLt
(
minus_SNo
x2
)
(
minus_SNo
x3
)
)
)
(
∀ x3 .
x3
∈
SNoR
x2
⟶
SNoLt
(
minus_SNo
x3
)
(
minus_SNo
x2
)
)
)
(
SNoCutP
(
prim5
(
SNoR
x2
)
minus_SNo
)
(
prim5
(
SNoL
x2
)
minus_SNo
)
)
)
⟶
SNoLev
x1
∈
SNoLev
x0
⟶
x1
∈
SNoS_
(
SNoLev
x0
)
⟶
and
(
and
(
SNo
(
minus_SNo
x1
)
)
(
∀ x2 .
x2
∈
SNoL
x1
⟶
SNoLt
(
minus_SNo
x1
)
(
minus_SNo
x2
)
)
)
(
∀ x2 .
x2
∈
SNoR
x1
⟶
SNoLt
(
minus_SNo
x2
)
(
minus_SNo
x1
)
)
(proof)
Known
and4I
and4I
:
∀ x0 x1 x2 x3 : ο .
x0
⟶
x1
⟶
x2
⟶
x3
⟶
and
(
and
(
and
x0
x1
)
x2
)
x3
Known
SNo_minus_SNo
SNo_minus_SNo
:
∀ x0 .
SNo
x0
⟶
SNo
(
minus_SNo
x0
)
Known
SNoL_E
SNoL_E
:
∀ x0 .
SNo
x0
⟶
∀ x1 .
x1
∈
SNoL
x0
⟶
∀ x2 : ο .
(
SNo
x1
⟶
SNoLev
x1
∈
SNoLev
x0
⟶
SNoLt
x1
x0
⟶
x2
)
⟶
x2
Known
minus_SNo_Lt_contra
minus_SNo_Lt_contra
:
∀ x0 x1 .
SNo
x0
⟶
SNo
x1
⟶
SNoLt
x0
x1
⟶
SNoLt
(
minus_SNo
x1
)
(
minus_SNo
x0
)
Known
SNoR_E
SNoR_E
:
∀ x0 .
SNo
x0
⟶
∀ x1 .
x1
∈
SNoR
x0
⟶
∀ x2 : ο .
(
SNo
x1
⟶
SNoLev
x1
∈
SNoLev
x0
⟶
SNoLt
x0
x1
⟶
x2
)
⟶
x2
Theorem
cf6dd..
Conj_minus_SNo_prop1__9__3
:
∀ x0 .
SNo
x0
⟶
(
∀ x1 .
x1
∈
SNoS_
(
SNoLev
x0
)
⟶
and
(
and
(
and
(
SNo
(
minus_SNo
x1
)
)
(
∀ x2 .
x2
∈
SNoL
x1
⟶
SNoLt
(
minus_SNo
x1
)
(
minus_SNo
x2
)
)
)
(
∀ x2 .
x2
∈
SNoR
x1
⟶
SNoLt
(
minus_SNo
x2
)
(
minus_SNo
x1
)
)
)
(
SNoCutP
(
prim5
(
SNoR
x1
)
minus_SNo
)
(
prim5
(
SNoL
x1
)
minus_SNo
)
)
)
⟶
(
∀ x1 .
x1
∈
SNoL
x0
⟶
and
(
and
(
SNo
(
minus_SNo
x1
)
)
(
∀ x2 .
x2
∈
SNoL
x1
⟶
SNoLt
(
minus_SNo
x1
)
(
minus_SNo
x2
)
)
)
(
∀ x2 .
x2
∈
SNoR
x1
⟶
SNoLt
(
minus_SNo
x2
)
(
minus_SNo
x1
)
)
)
⟶
SNoCutP
(
prim5
(
SNoR
x0
)
minus_SNo
)
(
prim5
(
SNoL
x0
)
minus_SNo
)
⟶
and
(
and
(
and
(
SNo
(
minus_SNo
x0
)
)
(
∀ x1 .
x1
∈
SNoL
x0
⟶
SNoLt
(
minus_SNo
x0
)
(
minus_SNo
x1
)
)
)
(
∀ x1 .
x1
∈
SNoR
x0
⟶
SNoLt
(
minus_SNo
x1
)
(
minus_SNo
x0
)
)
)
(
SNoCutP
(
prim5
(
SNoR
x0
)
minus_SNo
)
(
prim5
(
SNoL
x0
)
minus_SNo
)
)
(proof)
Known
minus_SNo_Lev_lem2
minus_SNo_Lev_lem2
:
∀ x0 .
SNo
x0
⟶
SNoLev
(
minus_SNo
x0
)
⊆
SNoLev
x0
Theorem
49f1d..
Conj_minus_SNo_Lev_lem1__22__2
:
∀ x0 x1 .
TransSet
x0
⟶
(
∀ x2 .
x2
∈
x0
⟶
∀ x3 .
x3
∈
SNoS_
x2
⟶
SNoLev
(
minus_SNo
x3
)
⊆
SNoLev
x3
)
⟶
ordinal
(
SNoLev
x1
)
⟶
SNo
x1
⟶
SNoCutP
(
prim5
(
SNoR
x1
)
minus_SNo
)
(
prim5
(
SNoL
x1
)
minus_SNo
)
⟶
SNoLev
(
minus_SNo
x1
)
⊆
SNoLev
x1
(proof)
Known
add_SNo_ordinal_SL
add_SNo_ordinal_SL
:
∀ x0 .
ordinal
x0
⟶
∀ x1 .
ordinal
x1
⟶
add_SNo
(
ordsucc
x0
)
x1
=
ordsucc
(
add_SNo
x0
x1
)
Known
dneg
dneg
:
∀ x0 : ο .
not
(
not
x0
)
⟶
x0
Theorem
4d514..
Conj_add_SNo_ordinal_SL__14__0
:
∀ x0 x1 .
ordinal
x1
⟶
(
∀ x2 .
x2
∈
x1
⟶
add_SNo
(
ordsucc
x0
)
x2
=
ordsucc
(
add_SNo
x0
x2
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
ordinal
(
add_SNo
x0
x1
)
⟶
ordinal
(
ordsucc
x0
)
⟶
SNo
(
ordsucc
x0
)
⟶
add_SNo
(
ordsucc
x0
)
x1
=
ordsucc
(
add_SNo
x0
x1
)
(proof)
Theorem
36a11..
Conj_mul_SNo_eq__19__0
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
x2
x4
x5
=
x3
x4
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
e4f91..
Conj_mul_SNo_eq__20__3
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x7 .
SNo
x7
⟶
x2
x6
x7
=
x3
x6
x7
)
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x6
=
x3
x0
x6
)
⟶
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
36a11..
Conj_mul_SNo_eq__19__0
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
x2
x4
x5
=
x3
x4
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
e4f91..
Conj_mul_SNo_eq__20__3
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x7 .
SNo
x7
⟶
x2
x6
x7
=
x3
x6
x7
)
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x6
=
x3
x0
x6
)
⟶
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
36a11..
Conj_mul_SNo_eq__19__0
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
x2
x4
x5
=
x3
x4
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
e4f91..
Conj_mul_SNo_eq__20__3
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x7 .
SNo
x7
⟶
x2
x6
x7
=
x3
x6
x7
)
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x6
=
x3
x0
x6
)
⟶
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
3816f..
Conj_mul_SNo_eq__22__3
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
SNo
x1
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x7 .
SNo
x7
⟶
x2
x6
x7
=
x3
x6
x7
)
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x6
=
x3
x0
x6
)
⟶
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
x5
∈
SNoS_
(
SNoLev
x1
)
⟶
SNo
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Known
SNoR_SNoS_
SNoR_SNoS_
:
∀ x0 .
SNoR
x0
⊆
SNoS_
(
SNoLev
x0
)
Theorem
a3487..
Conj_mul_SNo_eq__18__4
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
SNo
x0
⟶
SNo
x1
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x7 .
SNo
x7
⟶
x2
x6
x7
=
x3
x6
x7
)
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x6
=
x3
x0
x6
)
⟶
x5
∈
SNoR
x1
⟶
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
36a11..
Conj_mul_SNo_eq__19__0
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
x2
x4
x5
=
x3
x4
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Theorem
e4f91..
Conj_mul_SNo_eq__20__3
:
∀ x0 x1 .
∀ x2 x3 :
ι →
ι → ι
.
∀ x4 x5 .
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x0
)
⟶
∀ x7 .
SNo
x7
⟶
x2
x6
x7
=
x3
x6
x7
)
⟶
(
∀ x6 .
x6
∈
SNoS_
(
SNoLev
x1
)
⟶
x2
x0
x6
=
x3
x0
x6
)
⟶
x4
∈
SNoS_
(
SNoLev
x0
)
⟶
SNo
x5
⟶
x2
x4
x1
=
x3
x4
x1
⟶
x2
x0
x5
=
x3
x0
x5
⟶
add_SNo
(
x2
x4
x1
)
(
add_SNo
(
x2
x0
x5
)
(
minus_SNo
(
x2
x4
x5
)
)
)
=
add_SNo
(
x3
x4
x1
)
(
add_SNo
(
x3
x0
x5
)
(
minus_SNo
(
x3
x4
x5
)
)
)
(proof)
Param
mul_SNo
mul_SNo
:
ι
→
ι
→
ι
Known
SNoLt_irref
SNoLt_irref
:
∀ x0 .
not
(
SNoLt
x0
x0
)
Known
SNoLt_tra
SNoLt_tra
:
∀ x0 x1 x2 .
SNo
x0
⟶
SNo
x1
⟶
SNo
x2
⟶
SNoLt
x0
x1
⟶
SNoLt
x1
x2
⟶
SNoLt
x0
x2
Theorem
3cff7..
Conj_mul_SNo_SNoR_interpolate__4__3
:
∀ x0 x1 x2 x3 x4 x5 .
SNo
x2
⟶
SNo
x3
⟶
SNoLt
x3
x2
⟶
SNoLt
(
add_SNo
x2
(
mul_SNo
x4
x5
)
)
(
add_SNo
x3
(
mul_SNo
x4
x5
)
)
⟶
SNoLt
x2
x3
⟶
SNoLt
x3
(
mul_SNo
x0
x1
)
(proof)
Theorem
3cff7..
Conj_mul_SNo_SNoR_interpolate__4__3
:
∀ x0 x1 x2 x3 x4 x5 .
SNo
x2
⟶
SNo
x3
⟶
SNoLt
x3
x2
⟶
SNoLt
(
add_SNo
x2
(
mul_SNo
x4
x5
)
)
(
add_SNo
x3
(
mul_SNo
x4
x5
)
)
⟶
SNoLt
x2
x3
⟶
SNoLt
x3
(
mul_SNo
x0
x1
)
(proof)
Known
double_eps_1
double_eps_1
:
∀ x0 x1 x2 .
SNo
x0
⟶
SNo
x1
⟶
SNo
x2
⟶
add_SNo
x0
x0
=
add_SNo
x1
x2
⟶
x0
=
mul_SNo
(
eps_
1
)
(
add_SNo
x1
x2
)
Theorem
7bd1d..
Conj_double_eps_1__1__1
:
∀ x0 x1 x2 .
SNo
x0
⟶
SNo
x2
⟶
add_SNo
x0
x0
=
add_SNo
x1
x2
⟶
SNo
(
add_SNo
x1
x2
)
⟶
x0
=
mul_SNo
(
eps_
1
)
(
add_SNo
x1
x2
)
(proof)
Param
SNoLe
SNoLe
:
ι
→
ι
→
ο
Theorem
fb18d..
Conj_SNo_approx_real_rep__1__0
:
∀ x0 x1 .
(
∀ x2 .
x2
∈
SNoS_
omega
⟶
(
∀ x3 .
x3
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x2
(
minus_SNo
x0
)
)
)
(
eps_
x3
)
)
⟶
x2
=
x0
)
⟶
SNo
x1
⟶
SNoLt
x0
x1
⟶
x1
∈
SNoS_
omega
⟶
SNoLt
0
(
add_SNo
x1
(
minus_SNo
x0
)
)
⟶
not
(
∀ x2 : ο .
(
∀ x3 .
and
(
x3
∈
omega
)
(
SNoLe
(
add_SNo
x0
(
eps_
x3
)
)
x1
)
⟶
x2
)
⟶
x2
)
⟶
x1
=
x0
⟶
∀ x2 : ο .
x2
(proof)
Param
lam
Sigma
:
ι
→
(
ι
→
ι
) →
ι
Theorem
3aca5..
Conj_real_add_SNo__23__14
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x2
(
ordsucc
x7
)
)
(
ap
x4
(
ordsucc
x7
)
)
)
)
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x3
(
ordsucc
x7
)
)
(
ap
x5
(
ordsucc
x7
)
)
)
)
x6
)
)
⟶
lam
omega
(
λ x6 .
add_SNo
(
ap
x2
(
ordsucc
x6
)
)
(
ap
x4
(
ordsucc
x6
)
)
)
∈
setexp
(
SNoS_
omega
)
omega
⟶
lam
omega
(
λ x6 .
add_SNo
(
ap
x3
(
ordsucc
x6
)
)
(
ap
x5
(
ordsucc
x6
)
)
)
∈
setexp
(
SNoS_
omega
)
omega
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x2
(
ordsucc
x7
)
)
(
ap
x4
(
ordsucc
x7
)
)
)
)
x6
)
(
add_SNo
x0
x1
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
x0
x1
)
(
add_SNo
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x2
(
ordsucc
x7
)
)
(
ap
x4
(
ordsucc
x7
)
)
)
)
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x2
(
ordsucc
x8
)
)
(
ap
x4
(
ordsucc
x8
)
)
)
)
x7
)
(
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x2
(
ordsucc
x8
)
)
(
ap
x4
(
ordsucc
x8
)
)
)
)
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
x0
x1
)
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x3
(
ordsucc
x7
)
)
(
ap
x5
(
ordsucc
x7
)
)
)
)
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x3
(
ordsucc
x8
)
)
(
ap
x5
(
ordsucc
x8
)
)
)
)
x6
)
(
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x3
(
ordsucc
x8
)
)
(
ap
x5
(
ordsucc
x8
)
)
)
)
x7
)
)
⟶
SNoCutP
(
prim5
omega
(
ap
(
lam
omega
(
λ x6 .
add_SNo
(
ap
x2
(
ordsucc
x6
)
)
(
ap
x4
(
ordsucc
x6
)
)
)
)
)
)
(
prim5
omega
(
ap
(
lam
omega
(
λ x6 .
add_SNo
(
ap
x3
(
ordsucc
x6
)
)
(
ap
x5
(
ordsucc
x6
)
)
)
)
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
56dcc..
Conj_real_add_SNo__30__7
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x3
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x3
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x5
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x2
(
ordsucc
x8
)
)
(
ap
x4
(
ordsucc
x8
)
)
)
)
x6
=
add_SNo
(
ap
x2
(
ordsucc
x6
)
)
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x3
(
ordsucc
x8
)
)
(
ap
x5
(
ordsucc
x8
)
)
)
)
x6
=
add_SNo
(
ap
x3
(
ordsucc
x6
)
)
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x2
(
ordsucc
x7
)
)
(
ap
x4
(
ordsucc
x7
)
)
)
)
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x3
(
ordsucc
x7
)
)
(
ap
x5
(
ordsucc
x7
)
)
)
)
x6
)
)
⟶
lam
omega
(
λ x6 .
add_SNo
(
ap
x2
(
ordsucc
x6
)
)
(
ap
x4
(
ordsucc
x6
)
)
)
∈
setexp
(
SNoS_
omega
)
omega
⟶
lam
omega
(
λ x6 .
add_SNo
(
ap
x3
(
ordsucc
x6
)
)
(
ap
x5
(
ordsucc
x6
)
)
)
∈
setexp
(
SNoS_
omega
)
omega
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
0e33e..
Conj_real_add_SNo__33__2
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x5
x6
)
(
ap
x5
x7
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x3
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x3
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x5
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x2
(
ordsucc
x8
)
)
(
ap
x4
(
ordsucc
x8
)
)
)
)
x6
=
add_SNo
(
ap
x2
(
ordsucc
x6
)
)
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x3
(
ordsucc
x8
)
)
(
ap
x5
(
ordsucc
x8
)
)
)
)
x6
=
add_SNo
(
ap
x3
(
ordsucc
x6
)
)
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
(
lam
omega
(
λ x7 .
add_SNo
(
ap
x2
(
ordsucc
x7
)
)
(
ap
x4
(
ordsucc
x7
)
)
)
)
x6
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
Theorem
c87d9..
Conj_real_add_SNo__35__13
:
∀ x0 x1 x2 x3 x4 x5 .
x0
∈
real
⟶
x1
∈
real
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x2
x6
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
add_SNo
(
ap
x2
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x2
x7
)
(
ap
x2
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x3
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x0
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x0
(
ap
x3
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x3
x6
)
(
ap
x3
x7
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
ap
x4
x6
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
add_SNo
(
ap
x4
x6
)
(
eps_
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
∀ x7 .
x7
∈
x6
⟶
SNoLt
(
ap
x4
x7
)
(
ap
x4
x6
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
(
add_SNo
(
ap
x5
x6
)
(
minus_SNo
(
eps_
x6
)
)
)
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNoLt
x1
(
ap
x5
x6
)
)
⟶
SNo
x0
⟶
SNo
x1
⟶
SNo
(
add_SNo
x0
x1
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x0
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x0
)
⟶
(
∀ x6 .
x6
∈
SNoS_
omega
⟶
(
∀ x7 .
x7
∈
omega
⟶
SNoLt
(
abs_SNo
(
add_SNo
x6
(
minus_SNo
x1
)
)
)
(
eps_
x7
)
)
⟶
x6
=
x1
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x2
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x2
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x4
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x3
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x3
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
x5
(
ordsucc
x6
)
∈
SNoS_
omega
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
SNo
(
ap
x5
(
ordsucc
x6
)
)
)
⟶
(
∀ x6 .
x6
∈
omega
⟶
ap
(
lam
omega
(
λ x8 .
add_SNo
(
ap
x2
(
ordsucc
x8
)
)
(
ap
x4
(
ordsucc
x8
)
)
)
)
x6
=
add_SNo
(
ap
x2
(
ordsucc
x6
)
)
(
ap
x4
(
ordsucc
x6
)
)
)
⟶
add_SNo
x0
x1
∈
real
(proof)
previous assets